Optic Disc Pit with Sectorial Retinitis Pigmentosa - Melike Balikoglu-Yilmaz; Muhittin Taskapili; Tolga Yilmaz; Mehmet Yasin Teke (Case Reports in Ophthalmological Medicine)
Sectorial retinitis pigmentosa (RP) and optic disc pit (ODP) are rare clinical conditions. We present a 40-year-old woman with a history of mild night blindness and decreased vision in the right eye for about 5 years. Fundus examination revealed retinal pigmentary changes in the superior and inferotemporal sectors covering the macula and reduced arterial calibre and ODP at the temporal edge of the optic disc. In addition, fundus autofluorescence, spectral-domain optical coherence tomography, fluorescein angiography, and multifocal electroretinogram scans confirmed these clinical findings. Visual acuity was decreased due to an atrophic-appearing foveal lesion. No intervention was suggested because of the poor visual potential. To the best of our knowledge, the present study is the first to describe coexistent optic disc pit and sectorial RP in the superior and inferotemporal sectors covering the macula in the same eye with figures.